Juridical Review of the Inconsistencies in Medical Practice Licensing in the Implementation of Telemedicine from the Perspective of Indonesian Health Law - Susanti, Novita Andrayani; Purwani , Sagung Putri M. E.; Jayantiari , I Gusti Agung Mas Rwa (Westscience Press, 2025)
This study aims to identify and analyze the legal inconsistencies in medical practice licensing within the implementation of telemedicine services in Indonesia. As the use of telemedicine continues to grow as an alternative means of delivering remote healthcare, various legal challenges have emerged, particularly concerning the validity of medical practice licenses across different jurisdictions, violations of standard operating procedures, and potential misuse of patient data. This research provides a comprehensive examination of the legal implications that may affect three key entities: doctors, other healthcare professionals, and telemedicine service providers. The analysis is conducted through the lens of civil, criminal, and administrative malpractice frameworks. The study also reviews relevant national regulations governing telemedicine practices, including the Medical Practice Law, the Health Law, Ministry of Health Regulations (Permenkes), and the Electronic Information and Transactions Law (ITE Law). The findings reveal significant legal gaps, especially in the recognition of practice licenses across regional boundaries, patient data security, and accountability in digital health services. This research offers legal policy recommendations, such as regulatory harmonization, strengthened oversight mechanisms, and enhanced legal capacity-building for healthcare professionals involved in telemedicine practices.